AI Recruiting Selection: Examining and Determining Psychological Aspects for Employees and Job Applicants - Setyoningtias, Khasdyah Dwi Dewi; Mahardiana, Lina; Moreno, Shaden Gibran; Riquelme, Leysie (KnE Social Sciences, 2025)
Artificial Intelligence (AI) has been shown to improve the efficacy and efficiency of organizational performance when used in the hiring and selection process. In order to prove the effectiveness of hiring and selection, Artificial Intelligence should be integrated with the efforts of employees and job seekers.This study aimed to discover and investigate the psychological effects of using AI in the hiring and selection process. There are four psychological factors for job seekers and eight factors for employees, according to an assessment of the research from reputable article sources. Organizations must concentrate on these psychological factors if they want to keep using AI for hiring and selection to make it a successful process.